IgA Vasculitis Mimicking Obstructed Umbilical Hernia and Presenting as Gastrosurgical Emergency - Pooja Agarwal; Harsh Shah; Jay Shah; Malhar Shah; Kalgi Baxi (Nepal Journal of Dermatology, Venereology & Leprology)
IgA vasculitis (previously known as Henoch-schonlein purpura) is a systemic vasculitis which is more common in children than in adults. The classical triad clinically suggests the diagnosis includes purpuric rash, arthritis and abdominal pain. We report a case of a forty-seven-year-old male presented with an acute abdomen to a gastro-surgeon, and on exploratory laparotomy, multiple petechial lesions were found on the entire intestinal walls. Multiple petechiae were present over both the legs and hands as well, which prompted a dermatological consult, and the diagnosis of IgA vasculitis was confirmed with histopathological and immunofluorescence evaluation of the skin lesions.